2020
DOI: 10.21203/rs.3.rs-106643/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Digital Survey on the Acceptance and Affordability of COVID 19 Vaccine among the People of West Bengal, India- A Survey Based Study

Abstract: Overview: Currently, multiple vaccines for coronavirus disease 2019 (COVID-19) are in clinical trials. In Oct-Nov 2020, 1078 individuals in West Bengal surveyed to evaluate possible acceptance rates, affordability and factors affecting the acceptance of a vaccine for COVID-19.Result: 77.27 percent of respondents reported that they would be very or very likely to take a vaccine for COVID-19, 5.3 percent don’t want to take vaccine and 12.24 don’t know about their decision. In that 58 percent respondents want to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The findings from the surveys emphasise the need for tailored strategies to address determinants of vaccine hesitancy in several LMICs. Two surveys from India [ 27 , 29 ] and one from Pakistan [ 30 ] showed lower rates of vaccine hesitancy, both in the general population (17%) and in health care workers (10.6% and 0.05%, respectively), compared to other LMICs such as Bangladesh. Two surveys from Bangladesh reported the prevalence of vaccine hesitancy ranging from 32.5% to 41% [ 25 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from the surveys emphasise the need for tailored strategies to address determinants of vaccine hesitancy in several LMICs. Two surveys from India [ 27 , 29 ] and one from Pakistan [ 30 ] showed lower rates of vaccine hesitancy, both in the general population (17%) and in health care workers (10.6% and 0.05%, respectively), compared to other LMICs such as Bangladesh. Two surveys from Bangladesh reported the prevalence of vaccine hesitancy ranging from 32.5% to 41% [ 25 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is somewhat reassuring that vaccine hesitancy on the whole in LMICs remains comparatively low as compared to HICs [ 6 ]. A high COVID-19 vaccine acceptance level in the overall Indian population coupled with hesitancy in certain population subgroups [ 6 , 7 , 14 , 27 , 29 ] pointed towards need to explore the causes or contexts of this hesitancy. Studies also suggest that localised pockets of hesitancy in otherwise well-vaccinated populations may emerge as an additional challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Gautam et al 41 checked the responder's affordability and concluded that most responders wish a cheap or a free vaccine from the government. Vaccine cost and effectiveness appear as essential factors to accept vaccination 42 .…”
Section: Discussionmentioning
confidence: 99%
“…22 A digital survey from West Bengal showed that 77.27% of respondents were very likely or likely to take a COVID-19 vaccine while 12.24% and 5.3% were hesitant and resistant respectively. 23 Delhi NCR Coronavirus telephone survey (23 December 2020 and 4 January 2021) from Delhi, Haryana, Rajasthan, and Uttar Pradesh found that 60% participants were willing to take vaccine and vaccine hesitancy was quite high (39%). 24 Some preliminary reports post vaccination drive in country gives information about vaccine hesitancy.…”
Section: Resultsmentioning
confidence: 99%